Can Low Intensity Strength Training Alone for Older Females Improve Cardiovascular and Functional Fitness? - Yunsik Kim; David Michael O'Sullivan (Asian Society of Kinesiology, 2023)
BACKGROUND Maintaining muscle mass and an efficient cardiovascular system is vital for healthy aging. OBJECTIVES This study investigates if a low intensity senior strength exercise program for the older females can have an effect cardiovascular function and improve senior functional fitness. METHODS There were 22 older females, randomly divided into a strength exercise (age: 72.18 ± 4.97 yrs; height: 1.54 ± 0.06 m; weight: 58.02 ± 7.29 kg; BMI:24.43 ± 2.69 kg/m2) and control group (age: 77.63 ± 4.96 yrs; height: 1.51 ± 0.05 m; weight: 53.66 ± 6.62 kg; BMI:23.54 ± 2.22 kg/m2). The strength exercise group participated three times per week for 20 weeks, while the control group did not do any additional treatment or exercise. Participants were tested pre and post strength exercise, and the data were statistically analyzed using two-way repeated measures Analysis of Variance (ANOVA), with a significance level of p <0.05. RESULTS The results show significant differences (p<0.001) in homocysteine levels, with an interaction effect between time and group. There were no differences in changes in erythrocyte sedimentation rate between groups (p=0.050). There was an interaction effect (p<0.001) for the six components of the senior fitness test and between group and time in systolic blood pressure, diastolic blood pressure, heart rate, and pulse pressure. CONCLUSION In conclusion the results suggest that low intensity strength exercise program can improved cardiovascular fitness related variables, and homocysteine, as well as functional fitness, blood pressure, heart rate and pulse pressure.